Kajian Daya Tarik Ruang Terbuka Hijau Publik di Kampung Hijau Gambiran, Kota Yogyakarta - Dewi Setyaningrum; Retno Susanti (Jurusan Perencanaan Wilayah dan Kota, 2019)
Public green open spaces in Gambiran Green Village include Gajahwong Educational Park, Taman Krida, and Wifi Park. However, not all parks are utilized by the community, there are parks that have minimal daily visitors. This causes negative impacts such as parks prone to crime and used for immoral activities that disturb the surrounding environment. The malfunction of the park in Gambiran Green Village also caused the construction of the park to be redundant. The research method used is a quantitative approach with content analysis techniques. Based on the analysis done, it can be concluded that the attractiveness of a public green open space in Kampung Hijau Gambiran is strongly influenced by the availability of facilities (both primary and supporting facilities) and vegetation in the park; ability to accommodate community activities; and the location and accessibility of the park. Gajahwong Educational Park was chosen as the most attractive public green open space, in addition to the availability of facilities and vegetation that support the theme of education, but also because it has a broad and attractive design. Whereas Taman Krida was chosen as the least attractive public green open space due to the lack of socialization related to the existence of the public open space. The attractiveness of public green open spaces that can be sought at the thematic parks in Gambiran Green Village includes the improvement and addition of park facilities, as well as the addition of plant variations; creating a comfortable atmosphere for the community; optimization of park management involving the community; an inclusive park that can accommodate all activities.